Study on the mechanism of antibacterial action of magnesium oxide nanoparticles against foodborne pathogens - He, Yiping (J Nanobiotechnology, 2016)
BACKGROUND: Magnesium oxide nanoparticles (MgO nanoparticles, with average size of 20 nm) have considerable potential as antimicrobial agents in food safety applications due to their structure, surface properties, and stability. The aim of this work was to investigate the antibacterial effects and mechanism of action of MgO nanoparticles against several important foodborne pathogens. RESULTS: Resazurin (a redox sensitive dye) microplate assay was used for measuring growth inhibition of bacteria treated with MgO nanoparticles. The minimal inhibitory concentrations of MgO nanoparticles to 10(4) colony-forming unit/ml (CFU/ml) of Campylobacter jejuni, Escherichia coli O157:H7, and Salmonella Enteritidis were determined to be 0.5, 1 and 1 mg/ml, respectively. To completely inactivate 10(8−9) CFU/ml bacterial cells in 4 h, a minimal concentration of 2 mg/ml MgO nanoparticles was required for C. jejuni whereas E. coli O157:H7 and Salmonella Enteritidis required at least 8 mg/ml nanoparticles. Scanning electron microscopy examination revealed clear morphological changes and membrane structural damage in the cells treated with MgO nanoparticles. A quantitative real-time PCR combined with ethidium monoazide pretreatment confirmed cell membrane permeability was increased after exposure to the nanoparticles. In a cell free assay, a low level (1.1 μM) of H(2)O(2) was detected in the nanoparticle suspensions. Consistently, MgO nanoparticles greatly induced the gene expression of KatA, a sole catalase in C. jejuni for breaking down H(2)O(2) to H(2)O and O(2). CONCLUSIONS: MgO nanoparticles have strong antibacterial activity against three important foodborne pathogens. The interaction of nanoparticles with bacterial cells causes cell membrane leakage, induces oxidative stress, and ultimately leads to cell death.